Health literacy in familial hypercholesterolemia: A cross-national study - Hagger, Martin; Hardcastle, Sarah; Hu, M.; Kwok, S.; Lin, J.; Nawawi, H.; Pang, J.; Santos, R.; Soran, H.; Su, T.; Tomlinson, B.; Watts, G. (Sage Publications, 2018)
Background: High rates of inadequate health literacy are associated with maladaptive health outcomes in chronic disease including increased mortality and morbidity rates, poor treatment adherence and poor health. Adequate health literacy may be an important factor in the effective treatment and management of familial hypercholesterolemia, and may also be implicated in genetic screening for familial hypercholesterolemia among index cases. The present study examined the prevalence and predictors of health literacy in familial hypercholesterolemia patients attending clinics in seven countries. Design: Cross-sectional survey. Methods: Consecutive FH patients attending clinics in Australia, Brazil, China, Hong Kong, Malaysia, Taiwan and the UK completed measures of demographic variables (age, gender, household income and highest education level) and a brief three-item health literacy scale. Results: Rates of inadequate health literacy were lowest in the UK (7.0%), Australia (10.0%), Hong Kong (15.7%) and Taiwan (18.0%) samples, with higher rates in the Brazil (22.0%), Malaysia (25.0%) and China (37.0%) samples. Income was an independent predictor of health literacy levels, accounting for effects of age. Health literacy was also independently related to China national group membership. Conclusions: Findings indicate non-trivial levels of inadequate health literacy in samples of familial hypercholesterolemia patients. Consistent with previous research in chronic illness, inadequate health literacy is related to income as an index of health disparities. Chinese familial hypercholesterolemia patients are more likely to have high rates of inadequate health literacy independent of income. Current findings highlight the imperative of education interventions targeting familial hypercholesterolemia patients with inadequate health literacy.